-4(5x-4)+3(4x+2)=

Simple and best practice solution for -4(5x-4)+3(4x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5x-4)+3(4x+2)= equation:


Simplifying
-4(5x + -4) + 3(4x + 2) = 0

Reorder the terms:
-4(-4 + 5x) + 3(4x + 2) = 0
(-4 * -4 + 5x * -4) + 3(4x + 2) = 0
(16 + -20x) + 3(4x + 2) = 0

Reorder the terms:
16 + -20x + 3(2 + 4x) = 0
16 + -20x + (2 * 3 + 4x * 3) = 0
16 + -20x + (6 + 12x) = 0

Reorder the terms:
16 + 6 + -20x + 12x = 0

Combine like terms: 16 + 6 = 22
22 + -20x + 12x = 0

Combine like terms: -20x + 12x = -8x
22 + -8x = 0

Solving
22 + -8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-22' to each side of the equation.
22 + -22 + -8x = 0 + -22

Combine like terms: 22 + -22 = 0
0 + -8x = 0 + -22
-8x = 0 + -22

Combine like terms: 0 + -22 = -22
-8x = -22

Divide each side by '-8'.
x = 2.75

Simplifying
x = 2.75

See similar equations:

| 6n-3=3n-15 | | 2(2x+2)-3(x-4)= | | A/2=36 | | 84=78+n | | -x+7x=-12 | | -x^2+5=(4x-1)(4x-1) | | 4a+7a=7a+16 | | v/-4=13 | | -0.25+0.6= | | -0.25-0.6= | | (13m-11)=2m+5 | | -6(b-6)+4=88 | | 4.5s-s= | | 0.25-0.6= | | x*3+75=x*9-9 | | 18x11/(18x11)= | | 13m-11=2m+5 | | 2v-1=11 | | 63=2(6x-1)+5 | | 16a-5a= | | d+d+3d= | | -66=6(1+4m) | | 8(4n+2)=240 | | -3(2x-4)+(5x-3)= | | 11h+h= | | 3M-2p=0 | | 6-p^2=47 | | -(4x+6)-3(3x+6)= | | -8+4x=12+9x | | 5(2n-6)=-110 | | LA=3.14(r)(s) | | 4•/•2 |

Equations solver categories